2017
DOI: 10.1021/acs.nanolett.6b05412
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Three-Dimensional Graphene-Based Polyhedrons Inducing Volumetric Light Confinement

Abstract: The ability to transform two-dimensional (2D) materials into a three-dimensional (3D) structure while preserving their unique inherent properties might offer great enticing opportunities in the development of diverse applications for next generation micro/nanodevices. Here, a self-assembly process is introduced for building free-standing 3D, micro/nanoscale, hollow, polyhedral structures configured with a few layers of graphene-based materials: graphene and graphene oxide. The 3D structures have been further m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 44 publications
0
58
1
Order By: Relevance
“…Beyond assembling 2D materials relying on nucleation, and organizing 3D architecture depending on van der Waals forces, additional mechanism such as surface tension force can also impart new self‐assembly ways. Joung et al reported a micro/nanoscale self‐folding graphene‐based cube by surface tension forces of the polymer . As shown in Figure h, six graphene squares on protection layers are fabricated.…”
Section: Fabrication Of Patterned 2d Materialsmentioning
confidence: 99%
“…Beyond assembling 2D materials relying on nucleation, and organizing 3D architecture depending on van der Waals forces, additional mechanism such as surface tension force can also impart new self‐assembly ways. Joung et al reported a micro/nanoscale self‐folding graphene‐based cube by surface tension forces of the polymer . As shown in Figure h, six graphene squares on protection layers are fabricated.…”
Section: Fabrication Of Patterned 2d Materialsmentioning
confidence: 99%
“…Scale bar represents 100 µm. Reproduced with permission . Copyright 2017, American Chemical Society.…”
Section: Applicationsmentioning
confidence: 99%
“…Self‐folding cubes can be used as a scaffold to suspend novel atomistic materials such as graphene and graphene oxide to create novel electromagnetic devices . Joung et al demonstrated tunable optically transparent self‐folded polyhedra with freestanding graphene oxide panels and solder hinges (Figure e) .…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Joung et al reported the self‐folding of graphene by capillary force, using SU‐8 as a frame to support the flexible graphene pattern ( Figure a) . An SPR 200 polymer was used as the hinge to connect the SU‐8‐enhanced graphene flakes, and supply the driving force of the folding process when the sacrificial layer is removed and the temperature is above its melting point (≈100 °C).…”
Section: Fabrication Techniquesmentioning
confidence: 99%